Determining what is important for sustainability: scoping processes of sustainability assessments. Issue 1 (2nd January 2019) - Borgert, Thomas; Donovan, Jerome D; Topple, Cheree; Masli, Eryadi K
ABSTRACT: Over recent decades, there has been a significant proliferation of types of impact assessments. While some argue that this is threatening future use of impact assessments, sustainability assessments have emerged as a potential approach to bridge these diverse approaches. This research focuses on examining sustainability assessments at the project level, looking specifically at scoping practices key to integration. Nine multinational enterprises operating within Indonesia are studied, utilising a case study methodology with semi-structured interviews with 32 respondents. Findings emphasise that while these multinationals sought to address key regulatory requirements through their scoping practices, international standards and global sustainability platforms were critical in informing the practices of these organisations. The recognition of these standards and guidelines saw them addressing a broad range of key sustainability issues; also using prescribed techniques to engage with stakeholders and identify the most critical sustainability issues to focus on in assessment. There was integration of scoping processes through different levels and across the organisations, which were generally managed by teams providing sustainability expertise, including through affiliate personnel for local contextualisation. Abbreviation AMDAL - Analisis Mengenai Dampak Lingkungan (EIA); BAPEDALDA - provincial/regional-level of the Environmental Impact Management Agency; CAQDAS – computer assisted data analysis software; CSR – corporate social responsibility; EIA – environmental impact assessment; EU – European Union; FDI – foreign direct investment; GRI – Global Reporting Initiative; ILO – International Labour Organization; MCA – multicriteria analysis; MNE – multinational enterprise; MOE - Ministry of Environment (now Ministry of Environment and Forestry); NGO – non-government organisation; OECD – Organisation for Economic Cooperation and Development; OH&S – occupational health and safety; SPPL - Letter of Statement on Environmental Management Effort; UKL – Environmental Management Effort; UN – United Nations; UNGC – United Nations Global Compact; UPL - Environmental Controlling Effort.